"Smart" membrane controls how charge flows inside a battery. Issue 2 (February 2017) - Unknown
Abstract : In the USA, engineers at Ohio State University have developed a thin, plastic membrane that stops rechargeable batteries from discharging when they are not in use and enables them to be recharged rapidly. The technology has the potential to enable electric cars to travel further for each minute of charging.